Code Mixing for Beginner Japanese Language Learners at Mirai Mandiri - Putu Dewi Merlyna Y. P. (Jurnal Pedagogi dan Pembelajaran, 2023)
In a bilingual society, language contact always occurs along with misunderstandings in conveying messages or information. The purpose of this research is to find out the use of code mixing in the interaction process between elementary school students who are taking a Japanese language course for beginner classes and teachers at the Mirai Mandiri Japanese Language Course, the type of code-mixing that is spoken and the form of grammatical code-mixing phenomenon to be used in communicating process. This study uses a qualitative descriptive method. The research subjects were 15 elementary school students who were members of elementary level class groups, as well as a Japanese language teacher. The data collection technique used is the Uninvolved Conversation Observation Technique. Methods of data analysis using the equivalent method. The results of this study are that there are three types of code mixing used by elementary school students who learn Japanese as beginners when interacting with teachers or when interacting with fellow friends. The types of code mixing used are outer, inner, and mixed code-mixing. The used grammatical form is insertion.